Effects of Otarian Gymnastics on Malondialdehyde (GoM) Levels in Postpartum Women - Tut Barkinah; Januarsih Januarsih; Isnaniah Isnaniah (Jurnal Penelitian Pendidikan IPA, 2023)
If a woman is in a physiological postpartum condition, her body will increase the production of free radicals. This situation will be worse if the woman is undergoing pathological postpartum, the production of free radicals in her body will be even greater. This condition is known as oxidative stress. This situation can be prevented by postpartum mothers doing Otaria exercises. The design used in this research was Post Test Only Control Group Design or Post-test with an experimental group of 20 respondents and 20 respondents in a control group of 20 respondents. The research was conducted in the PKM Karang Intan 2 working area, Banjar Regency, South Kalimantan Province, which includes 13 villages. The research instrument or measuring tool used to see the effect of exercise on MDA levels in postpartum mothers is the GoM Assay Kit (TBA method) from Assay Genie with product catalog: MAES0037. In the treatment group with a low average GoM, it can be seen that the average GoM shows an increase in the control group. This shows that Otaria exercise is able to reduce GoM levels significantly. Oxidative stress can be prevented with antioxidants as a mechanism for the body's defense system against free radicals. Oxidative stress in mothers during the post-partum period can be prevented by doing Otaria exercises which have been proven to be able to reduce GoM levels in post-partum maternal plasma